Buying and Selling System at the Honesty Canteen in Banjarmasin City from the Syafi'i Madzhab Perspective - Badruddin Ibad (Yayasan Adra Karima Hubbi, 2024)
Some schools in Banjarmasin, like SMP 7, use the honest canteen as a government and school strategy to promote honesty among all pupils. Without ever having to interact with the vendor in person, customers of a